Sarcoplasmic reticulum Ca2+, Mg2+, K+, and Cl− concentrations adjust quickly as heart rate changes. (February 2017) - Berti, Claudio; Zsolnay, Vilmos; Shannon, Thomas R.; Fill, Michael; Gillespie, Dirk
Abstract: During systole, Ca 2+ is released from the sarcoplasmic reticulum (SR) through ryanodine receptors (RyRs) while, simultaneously, other ions (specifically K +, Mg 2+, and Cl − ) provide counter-ion flux. These ions move back into the SR during diastole through the SERCA pump and SR K + and Cl − channels. In homeostasis, all ion concentrations in different cellular regions (e.g., junctional and non-junctional SR, dyadic cleft, and cytosol) are the same at the beginning and end of the cardiac cycle. Here, we used an equivalent circuit compartment model of the SR and the surrounding cytoplasm to understand the heart rate dependence of SR ion homeostasis. We found that the Ca 2+, Mg 2+, K +, and Cl − concentrations in the SR and the cytoplasm self-adjust within just a few heartbeats with only very small changes in Mg 2+, K +, and Cl − concentrations and membrane voltages (just a few percent). However, those small changes were enough to compensate for the large heart-rate-dependent changes in SR and cytoplasmic Ca 2+ concentrations in the new steady state. The modeling suggests that ion adaptation to increases in heart rate is inherent to the system and that physiological changes that increase contractility and cardiac output are accommodated by the same self-adjusting mechanism of producing small changes in ion driving forces. Our findings also support the long-held hypothesis that SR membrane potentials are small ( 1–2 mV). Highlights: Cardiac excitation/contraction coupling is modeled with an equivalent circuit. How heart rate affects the compartments' [Ca 2 + ], [K + ], [Mg 2 + ] and [Cl − ] is studied. As heart rate increases, [K + ], [Mg 2 + ], [Cl − ], and voltage changes are very small. These small changes are enough to compensate for large [Ca 2 + ] changes. New ion homeostasis is reached within a few heartbeats even at high pacing rates.